2009
DOI: 10.1093/humrep/den490
|View full text |Cite
|
Sign up to set email alerts
|

Maternal levels of perfluorinated chemicals and subfecundity

Abstract: These findings suggest that PFOA and PFOS exposure at plasma levels seen in the general population may reduce fecundity; such exposure levels are common in developed countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
200
7
19

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(241 citation statements)
references
References 27 publications
15
200
7
19
Order By: Relevance
“…Nearly all compounds measured in the present study can be categorized as endocrine disruptors, some of which have been suspected to affect the reproductive system in males, as well as play an important role in the decline of semen quality and increase in testicular cancer in Denmark (61)(62)(63). Effects on reproduction in females have also been reported for compounds measured in the present study (64)(65)(66)(67). Furthermore, neurological and immunological effects have been associated to chemical exposure (28,58,68,69).…”
Section: All Biomarkers In the Studysupporting
confidence: 62%
“…Nearly all compounds measured in the present study can be categorized as endocrine disruptors, some of which have been suspected to affect the reproductive system in males, as well as play an important role in the decline of semen quality and increase in testicular cancer in Denmark (61)(62)(63). Effects on reproduction in females have also been reported for compounds measured in the present study (64)(65)(66)(67). Furthermore, neurological and immunological effects have been associated to chemical exposure (28,58,68,69).…”
Section: All Biomarkers In the Studysupporting
confidence: 62%
“…Weak associations between PFOA and PFOS exposure and reduced fertility in humans have been observed (Fei et al, 2009;Whitworth et al, 2012). A few human studies have also shown positive but weak associations between PFOA or PFOS exposure and preeclampsia, early menopause, delayed puberty onset, and semen quality, while other studies have shown no association with some of these reproductive parameters (Fei et al, 2009;Stein et al, 2009;Knox et al, 2011;Lopez-Espinosa et al 2011;Joensen et al 2009;Raymer et al 2012;Louis et al 2013). However, a recent prospective study shows an association between in utero exposure to PFOA and semen quality and reproductive hormones in male offspring 20 years later.…”
Section: Reproductive and Developmental Toxicitymentioning
confidence: 99%
“…Sperm concentration, total sperm count and semen volume was not consistently associated with PFOA. Couple fecundity and time to pregnancy (TTP) were evaluated in the Danish National Birth Cohort study (n = 1,240) (Fei et al, 2009). The evaluation of TTP showed increased risk of irregular menstrual cycles in the upper three quartiles of PFOA relative to the lowest quartile and an increase in mean PFOA with longer TTP.…”
Section:  Reproductive Effectsmentioning
confidence: 99%